Bloch oscillations of multidimensional dark soliton wave packets and light bullets - Driben, R; Ma, Xuekai; Schumacher, Stefan; Meier, Torsten (Optics Letters)

Vortex Multistability and Bessel Vortices in Polariton Condensates. - Ma, Xuekai; Schumacher, Stefan (Physical Review Letters)

Two-dimensional symbiotic solitons and vortices in binary condensates with attractive cross-species interaction - Ma, Xuekai; Driben, Rodislav; Malomed, Boris A.; Meier, Torsten; Schumacher, Stefan (Scientific Reports)

Stochastic pumping of a polariton fluid - Assmann, Marc; Bayer, Manfred (PHYSICAL REVIEW A)
We investigate the response of a polariton laser driven slightly off-resonantly using light fields differing from the routinely studied coherent pump sources. The response to driving light fields with thermal and displaced thermal statistics with varying correlation times shows significant differences in the transmitted intensity, its noise, and the position of the nonlinear threshold. We predict that adding more photons on average may actually reduce the transmission through the polariton system.

Photon-Statistics Excitation Spectroscopy of a Quantum-Dot Micropillar Laser - Kazimierczuk, T.; Schmutzler, J.; Aßmann, M.; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M. (Physical Review Letters)
We introduce photon-statistics excitation spectroscopy and exemplarily apply it to a quantum-dot micropillar laser. Both the intensity and the photon number statistics of the emission from the micropillar show a strong dependence on the photon statistics of the light used for excitation of the sample. The results under coherent and pseudothermal excitation reveal that a description of the laser properties in terms of mean input photon numbers is not sufficient. It is demonstrated that the micropillar acts as a superthermal light source when operated close to its threshold. Possible applications for important spectroscopic techniques are discussed.